Analysis of bacterial community and bacterial nutritional enzyme activity associated with the digestive tract of wild Chilean octopus (Octopus mimus Gould, 1852). (15th July 2013) - Iehata, Shunpei; Valenzuela, Fernando; Riquelme, Carlos
Abstract Information on the bacterial community associated with octopus is very scarce, unlike fish and other molluscs. This study revealed the bacterial community associated with digestive tract of wild Chilean octopus Octopus mimus using a culture‐dependent method and 16S rDNA clone library. Moreover, we analysed the bacterial nutritional enzyme activity of culturable bacteria. A culture‐dependent method showed that the composition of the culturable bacterial community was substantially different between female and male octopus. The predominant species in female octopus were Vibrionaceae and Streptococcaceae, whereas only Vibrionaceae was dominated in male octopus. Bacterial nutritional enzyme activities of culturable bacteria from male octopus were much higher than female octopus. The 16S rDNA clone library analysis showed that the bacterial community of male octopus exhibited a higher diversity than that of female octopus. The genus Mycoplasma was the predominant bacteria in the digestive tract of all octopus samples. The results obtained in this study raise the possibility that each octopus has different food consumption due to different bacterial community and nutritional enzyme activity, although Mycoplasma sp. is one of the predominant bacteria in the digestive tract. Moreover, our results are useful for the future of microbiological investigation associated with the octopus and for probiotics in the octopus aquaculture.